Microbial composition, assembly, and functional characteristics of generalized and specialized subcommunities under flooded paddy fields: long-term pesticide versus non-pesticide models - Wang, Jing-Wen; Han, Cai-Ting; Wu, Dong-Ming; Zhou, Wei; Gao, Miao; Li, Yu-Shuang (Frontiers in Microbiology, 2025)
BackgroundThe extensive application of pesticides in agricultural practices is known to affect microbial health and thus eco-multifunctionality in soil. However, previous studies have mainly focused on these effects on whole microbial community in dryland, without considering that in paddy fields under flooded condition, especially lacking the finer insights into subcommunities related to niche fitness.MethodsTo address this issue, the paddy fields, managed with (HP) and without pesticide application (HH) over 8 years, were selected. Then, the occurrence characteristics, function and assembly of generalized and specialized subcommunities classified by niche fitness were investigated.ResultsThe findings revealed that compared to HP model, the microbiota under HH model displayed higher bacterial diversity in both specialists and generalists, as well as greater fungal diversity in the generalists. However, pesticide residues in HP treatment increased copiotrophic microorganisms (e.g., Gemmatimonadota) in paddy soil, whereas oligotrophic microorganisms (e.g., Proteobacteria and Acidobacteriota) were significantly reduced. This indicated a special response of microflora to pesticide application under flooded condition, challenging the traditional views. Despite these changes, HP treatment also exhibited a substantial rise in pathogenic Fusarium, implying a higher diseases risk for rice. Neutral modeling revealed that both bacterial and fungal communities in HP were primarily driven by deterministic processes. Especially for specialists, it had a homogenization selection and diffusional limitation during community succession, because it was characterized by constrained adaptability, narrow ecological niches and high resource specificity. Regarding microbial networks, HP treatment resulted in lower node degree and closeness centrality compared to HH, leading to a decline in the overall functional capacity of the microbial community. FAPROTAX functional predictions further observed a significant reduction in the genes associated with nitrogen cycle and cellulolysis, while the human disease-related genes were increased in HP treatment. Collectively, these findings reveal that pesticide application in paddy fields significantly impacts microbial community structure and function, with specialized subcommunities being particularly vulnerable. These findings broaden our understanding into assembly principles of specialists and generalists under pesticide application in flooded paddy, which will contribute to the sustainable management for rice cultivation.